Validation and Clinical Applications of a Comprehensive Next Generation Sequencing System for Molecular Characterization of Solid Cancer Tissues - Dehghani, Mehdi; Rosenblatt, Kevin P.; Li, Lei; Rakhade, Mrudula; Amato, Robert J. (Frontiers in Molecular Biosciences, 2019)
Identification of somatic molecular alterations in primary and metastatic solid tumor specimens can provide critical information regarding tumor biology and its heterogeneity, and enables the detection of molecular markers for clinical personalized treatment assignment. However, the optimal methods and target genes for clinical use are still being in development. Toward this end, we validated a targeted amplification-based NGS panel (Oncomine comprehensive assay v1) on a personal genome machine sequencer for molecular profiling of solid tumors. This panel covers 143 genes, and requires low amounts of DNA (20 ng) and RNA (10 ng). We used 27 FFPE tissue specimens, 10 cell lines, and 24 commercial reference materials to evaluate the performance characteristics of this assay. We also evaluated the performance of the assay on 26 OCT-embedded fresh frozen specimens (OEFF). The assay was found to be highly specific (>99%) and sensitive (>99%), with low false-positive and false-negative rates for single-nucleotide variants, indels, copy number alterations, and gene fusions. Our results indicate that this is a reliable method to determine molecular alterations in both fixed and fresh frozen solid tumor samples, including core needle biopsies.